Ischemic stroke in patients with congenital heart disease and atrial fibrillation. (3rd October 2022) - Holmgren, A; Dellborg, M; Mandalenakis, Z; Giang, K W; Eriksson, P; Fedchenko, M
Abstract: Background: Atrial fibrillation (AF) is one of the most common arrhythmias in patients with congenital heart disease (CHD). The risk of developing AF is more than 20 times higher in patients with CHD compared with non-CHD controls. However, while it is known that young non-CHD patients with AF have a low risk for ischemic stroke (IS), little is known about the risk for IS young CHD patients with AF. Purpose: To investigate the risk of developing IS in younger patients with CHD and AF compared to non-CHD control patients with AF. Method: Using data from the National Swedish Patient Register and Cause of Death register, all CHD and born in Sweden between 1970 and 2017 with history of AF were identified. The Swedish total population register was used to identify age and sex matched controls. Among the matched controls, non-CHD patients AF were identified and used as reference group. CHD and non-CHD patients were followed from onset of AF until index IS, death or end of study (31st December 2017). Cox proportional hazard regression model with hazard ratio (HR) and 95% confidence interval (CI) was used to estimate the risk of IS in CHD patients with AF compared with non-CHD controls with AF. Results: A total of 951 CHD with AF and 606 non-CHD controls with AF were identified. With ages ranging from 0 to 47 years, the median age was 25.6 and 30.7 years for CHD and non-CHD respectively. In patients with CHD and AF, 2.9% of patients (n=28) developed IS during follow up (mean follow up 34 years, SD ± 11.2), compared 0.5% (n=3) in non-CHD controls with AF (mean follow up 37 years, SD ± 9.5 years). The unadjusted HR for IS in CHD patients with AF compared with non-CHD controls with AF was 4.61 (95% CI1.39–15.25). When adjusted for age, sex, hypertension and heart failure, the risk of IS was more than five times higher (HR 5.16, 95% CI 1.52–17.46) in CHD patients compared with non-CHD patients. The adjusted HR for developing IS in non-complex CHD with AF compared with matched controls was 4.56 (95% CI 1.00–20.79). For patients born 1970–1989 the HR of IS was 7.35 (95% CI 1.70–31.75). Conclusion: In this nationwide, register-based cohort study, the absolute number of IS among younger CHD patients with AF was relatively low. However, the risk for developing IS was more than 5 times higher compared to non-CHD patients with AF; highlighting the need of stroke score models in younger population, particularly to CHD patients. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Swedish state under an agreement between the Swedish government and city Councils